1991
DOI: 10.1002/jrs.1250221114
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonding and the liquid‐to‐glass transition in propan‐1‐ and ‐2‐ol at high pressures

Abstract: The pressure dependence of the vibrational modes of propan-1-and 2-01 was measured by Raman spectrwopy up to 8 GPa at 300 K. Changes in the observed vibrational spectra indicate that the samples undergo a liquid-teglass transition at about 4.5 GPa for propan-%ol and about 5.5 GPa for propan-1-01. The frequency of the 0-H stretching mode (a probe of the degree of hydrogen bonding) was found to decrease at a rate of cu -28 cm-' GPa-' for both propan-1-and -2-01.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The value of P* -4.7 ± 0.3 GPa for 1,2-propanediol can be compared to the ruby fluorescence determinations of Pg = 4.4 GPa for glycerol and Pg * 4.3 GPa for 2-propanol.36 Yenice et al also reported glass transition pressures determined from Raman scattering measurements of 4.5 GPa for 1-propanol and 5.5 GPa for 2-propanol. 37 In decompression experiments, we observed the loss of pressure gradients at 2.2 GPa for dibutyl phthalate which compares with P* of 1.8 ± 0.1 GPa.…”
Section: Discussionmentioning
confidence: 64%
“…The value of P* -4.7 ± 0.3 GPa for 1,2-propanediol can be compared to the ruby fluorescence determinations of Pg = 4.4 GPa for glycerol and Pg * 4.3 GPa for 2-propanol.36 Yenice et al also reported glass transition pressures determined from Raman scattering measurements of 4.5 GPa for 1-propanol and 5.5 GPa for 2-propanol. 37 In decompression experiments, we observed the loss of pressure gradients at 2.2 GPa for dibutyl phthalate which compares with P* of 1.8 ± 0.1 GPa.…”
Section: Discussionmentioning
confidence: 64%